2012
DOI: 10.1260/1708-5284.9.5.451
|View full text |Cite
|
Sign up to set email alerts
|

Properties of knitted fabrics produced by kapok blended yarns

Abstract: In need of improving the properties of textiles, researchers investigate how to obtain surface with better mechanical and physical characteristics. On the other hand, for clothing purposes, it is also required to enhance comfortable properties. However, uniting these properties in the end product is difficult. For this objective, new fibers those allow what is desired are developed. This is one of the easiest ways. Because, if these characteristics can be found on the raw material, less treatments will be need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…Kapok liflerinin tohum çekirdeklerinden ayrılmasında kullanılan makinalar pamuk elyafında kullanılana benzer nitelikte olan çırçır makineleridir [7]. Çırçır işlemi sonrası kapok elyafı pamuk elyafında olduğu gibi balyalanarak depolanmaktadır [6,41]. Balyalama işleminin ortalama bir basınçta (5 kg/cm 2 ) gerçekleştirilmesi liflerin elastikiyetleri başta olmak üzere çeşitli lif özelliklerinin bozulmadan korunabilmesi için büyük önem taşımaktadır [6,7].…”
Section: şEkil 1 Kapok Ağacı Kapok Meyvesi Ve Kapok Lifleriunclassified
“…Kapok liflerinin tohum çekirdeklerinden ayrılmasında kullanılan makinalar pamuk elyafında kullanılana benzer nitelikte olan çırçır makineleridir [7]. Çırçır işlemi sonrası kapok elyafı pamuk elyafında olduğu gibi balyalanarak depolanmaktadır [6,41]. Balyalama işleminin ortalama bir basınçta (5 kg/cm 2 ) gerçekleştirilmesi liflerin elastikiyetleri başta olmak üzere çeşitli lif özelliklerinin bozulmadan korunabilmesi için büyük önem taşımaktadır [6,7].…”
Section: şEkil 1 Kapok Ağacı Kapok Meyvesi Ve Kapok Lifleriunclassified
“…Besides, kapok/cotton blended fiber appears to have comparable moisture permeability with pure cotton. In any case, the air permeability is decreased, and the warmth retention and water vapor transmission properties are upgraded owing to the exceptionally permeable construction of the kapok fiber [19][20][21]. It was reported that the moderate alkali treatment for kapok fiber, could be decreased the crystallinity of the blended yarns contrasted with cotton fiber [22,23].…”
Section: Introductionmentioning
confidence: 99%